'I am not a German Jew. I am a Jew with a German passport': German-Jewish identification among Jewish Germans and Jewish German Israelis. Issue 1 (2nd January 2018) - Hochman, Oshrat; Heilbrunn, Sibylle
ABSTRACT: The aim of this study is to explore the way German-Jews negotiate their German and Jewish cultural self-identifications. Given that Jewish and German identities represent both ethnic and national identities, we conceptualize their construction and reconstruction referring to theories of national identity. To describe the outcomes of the negotiation processes observed, we recruit Berry's acculturation theory. This theory provides a valuable framework to conceptualize the integration of two cultural self- identifications. The German-Jewish-Israeli setting is particularly interesting due to the complex relations between the three social groups emerging in the aftermath of the Holocaust. To explore the participants' German, Jewish and Israeli self-identifications and the role of the Holocaust in their construction and reconstruction, we conducted 18 in-depth interviews. Findings imply that the Holocaust plays a role in the construction of an integrated German-Jewish identification. Yet, the Holocaust and its consequences notwithstanding, an integrated German-Jewish self-identification is possible.